1997
DOI: 10.1021/ac960693v
|View full text |Cite
|
Sign up to set email alerts
|

Flow Injection Fourier Transform Infrared Determination of Caffeine in Soft Drinks

Abstract: A fully automated procedure has been developed for FT-IR determination of caffeine in soft drinks. Samples are first degasified by filtration and then directly injected into a flow manifold and passed through a 100 mg C 18 SPE cartridge, conditioned with methanol and water. After the cartridge has been cleaned with water, the caffeine is eluted with CHCl 3 and stabilized with ethanol. The flow injection (FI) recording is obtained by measuring the absorbance at 1658 cm -1 with a baseline established at 1800 cm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…Caffeine has been determined in other beverages like coke [22] and coffee samples [23,24] by the use of FTIR spectrometry, because this technique offers an excellent sensitivity and selectivity for this kind of analysis being possible to do a practically direct determination after a simple solid phase [22] or a solvent extraction [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Caffeine has been determined in other beverages like coke [22] and coffee samples [23,24] by the use of FTIR spectrometry, because this technique offers an excellent sensitivity and selectivity for this kind of analysis being possible to do a practically direct determination after a simple solid phase [22] or a solvent extraction [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from that, caffeine is also found in other products that have gained popularity in the last years, like soft and energy drinks (Barone & Roberts 1996;Daghbouche et al 1997;Frary et al 2005), and its amount is higher than that found in coffee and tea beverages.…”
mentioning
confidence: 99%
“…Quantification was based on evaluation of the caffeine band at 1658 cm 1 with respect to a baseline point at 1800 cm 1 indicating successful replacement of water by organic solvents. 133 …”
Section: Automated Solvent Exchange During the Determination Of Caffementioning
confidence: 99%